Preferensi Intermoda di Stasiun Pekalongan dalam Pengembangan Pariwisata - Ameliya, Fita; Basuki, Yudi (Jurusan Perencanaan Wilayah dan Kota, 2024)
Efforts to grow the economy of a region can be done through one of the tourism development strategies. The diversity of tourism destinations in Indonesia reflects that the tourism sector is a priority sector to be developed. To restore the tourism sector after the COVID-19 pandemic, it can be supported by the provision of tourism transportation services. Various forms of transportation services can be an attraction for tourists if they prioritize comfort, safety, and convenience for tourism transportation users. Pekalongan City is one of the cities in Indonesia which is known as the 'Batik City'. Referred to as the 'Batik City', the tourism sector in Pekalongan City is one of the priority sectors. The existence of planning for the Transit Oriented Development (TOD) near Pekalongan Station causes the importance of developing forms of tourism transportation services such as intermodal services which are expected to be a connector between tourist objects. In addition, Pekalongan Station is also the most popular transportation by tourists compared to buses because it can be reached in a short time. The purpose of this research is to determine the preference of intermoda at Pekalongan Station as an effort to develop tourism based on the characteristics of tourist trips. The analysis was carried out using correspondence analysis with descriptive methods through a quantitative approach. The results of this study are that there are 3 modes of transportation that are trending, including private motorbikes, online motorbikes, and rental cars. Private motorbikes were chosen for reasons of low cost with preference for recreational and educational tourism objects, history, and culture. The online motorbike was chosen for the reason that it is easy to reach with a preference for culinary tourism objects. The rental car was chosen for reasons of convenience with preferences for religious tourism objects and shopping tours.